KEMUNCULAN TAHAP MENULIS ALFABET PADA GAMBAR EKSPRESIF ANAK USIA 5-6 TAHUN - Putri Megasari (JIV-Jurnal Ilmiah Visi, 2014)
This purpose of this study was to reveal the emergence of alphabetic writing stage of the expressive drawings of the children aged 5-6 years in Early Childhood Education Services Post in Kebayoran Lama, South Jakarta. The study, conducted October 2013, employed quantitative method using survei techniques. The participant of this research involved 75 children ranged from the ages of 5 years 0 month to 6 years. Data were collected by using structured interview guides and analyzed with percentage technique. The findings show that the emergence of alphabetic writing stage when the children are able to write letters and their own names appears at the age of 5 years 0 month. The emergence of writing integrated letters to form a word, phoneme writing, and word writing appears at the age of 5 years 1 month. The emergence writing short sentence appears as from the ages of 5 years 7 months to 6 years, while the emergence of writing story writing appears as from the ages of 5 years 10 months to 6 years. The findings have implication to the parents and teachers in identifying the development of the childrenâ€™s writing ability.